Lexical Features of Social Media Discourse - Halámka, Kryštof (Univerzita Pardubice, 2018)
This bachelor thesis deals with the use of non-standard lexical features on popular social media. The paper describes several issues related to social media discourse, the effects of language informality and spoken language on it, as well as the non-standard lexical features in detail. The analytical part of the thesis focuses on the use of specific non-standard lexical features, on the frequency of their occurrence within specific social media sites, as well as on their meaning and the authors' motivations for using them.
Lexikální rysy jazyka na sociálních sítích
Keywords: lexical features; social media; written discourse; communication; internet; language formality; lexikální rysy; sociální sítě; psaný jazyk; komunikace; internet; jazyková formalita